Bilateral ovarian Krukenberg tumor at mid-gestation - (:unkn) unknown (My University, 2014)
Gebelikte adneksiyal kitleler 1/81 ile 1/2,500 sıklıkta görülse de bunların sadece %3ü maligndir. Krukenberg tümörü, gastrik tümörün yumurtalıklara metastazıdır ve tüm over kanserlerinin %1-2sini oluşturur. Son bir haftada epigastrik ağrısı olan 29 yaşında 20.gestasyonel haftasında olan gravida 3, parite 2 bir kadın ünitemize refere edildi. Abdominal ultrasonografide 20 gebelik haftası ile uyumlu biyometrik ölçümleri olan bir bebek izlendi. Ayrıca her iki adneksiyal alana doğru uzanan rahimin arkasında yerleşimli 12,8 x 12 cm çapında solid kitle tespit edildi. Genel anestezi altında orta hat kesisi ile batına girildiğinde haftasıyla uyumlu büyüklükte gebe uterus izlendi. Sağ overden kaynaklanan 12 x 13 cm kitle eksize edildi. Sol overden kaynaklanan 17 x 18 cm kitle eksize edildi. Nihai patoloji sonucu pozitif batıniçi yıkama sıvısı ve her iki overe adenokarsinom metastazı olarak geldi. Üç hafta sonra yapılan gastroskopik biyopsinin patoloji sonucu midenin adenokarsinomu olarak geldi. Hastamız takiplere gelmedi.

Even though adnexal masses are detected during pregnancy ranging from 1 to 81 to 1 in 2.500 pregnancies, only 3% of these are malignant. A Krukenberg tumor is an ovarian metastasis of a gastric tumor and accounts for 1-2% of all ovarian tumors. A 29-year-old woman, gravida 3, para 2, was referred to our unit at 20 weeks gestation because of epigastric pain for the last one week. Her abdominal ultrasound revealed a singleton pregnancy, with fetal measurements compatible with 20 weeks of gestation. A solid mass of 12.8 cm by 12 cm localized posterior to the uterus extending to both adnexial regions was also detected. Under general anesthesia, a midline abdominal incision was made. During abdominal inspection the gravid uterus was the size appropriate for the current gestational week. A 12 cm by 13 cm mass originating from the right ovary was excised. Then, a 17 cm by 18 cm mass originating from the left ovary was excised. The final pathology report confirmed positive washing cytology and a metastastic adenocarcinoma of both ovaries. Three weeks later, the woman had a gastroscopic biopsy and the pathology report was of an adenocarcinoma of the stomach. Unfortunately, the woman was lost to follow-up.
İkinci trimesterde bilateral ovaryen Krukenberg tumörü
Keywords: Genel ve Dahili Tıp